Strategi Pengembangan Agribisnis Kentang Berbasis Sumber Daya Manajemen di Kabupaten Banjarnegara - Siti Leny Puspasari; Hartrisari Hardjomidjojo; Ma'mun Sarma (Institut Pertanian Bogor, 2013)
Horticulture is one of the agriculture sub-sector which is potential to be developed, because it has quite high economic value and added value compared to other commodities. One of horticultural commodity namely potato (Solanum Tuberosum) is a vegetable, which has an important role to fulfill food needs. Potato has potential and good prospect to support food diversification program in order to achieve sustainable food security. Potato commodity is one of the best commodities in Banjarnegara district. The study was aimed to (1) identify factors, that effect the agribusiness development of potato commodity through management resource approach in Banjarnegara district, (2) formulate agribusiness development strategy of potato commodity in Banjarnegara district and (3) determine the priority of alternative strategy for the agribusiness development of potato commodity in Banjarnegara district. Based on prospective analysis that there are 10 factors that effect the agribusiness development of potato commodity in Banjarnegara district. Agribusiness development strategy of potato commodity through management resource approach in Banjarnegara district is based on scenarios that the agribusiness will grow in the future. Based on AHP, the most influential factor in formulating agribusiness development strategy of potato commodity in Banjarnegara district is productivity.Key words: strategy development, agribusiness, potato, prospective analysis, analytical hierarchy process